POLA ASUH DEMOKRATIS ORANG TUA DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL ANAK DI POSYANDU SEJAHTERA - Ba' oen, Angie Ameldavita; Nugroho, Rivo (J+PLUS UNESA, 2024)
The development of emotional intelligence as one of human potential is in line with the task of education, which is to discover and develop the basic abilities possessed by young children, so that they can be actualized in everyday life. Emotional intelligence is also related to human potential as social creatures. The ideal parenting pattern in developing emotional intelligence is a democratic parenting pattern, that is, a parenting pattern with parents who are high in demands (demandingness) and responsiveness. Democratic parenting makes children become people who are willing to accept criticism, respect others, have high self-confidence and are able to take responsibility for their social life. This research aims to determine the influence of the role of democratic parenting used by parents in developing children's emotional intelligence, where researchers use qualitative research methods with data collection techniques using interviews and observation. The target of this research is parents who have young children. The research results show that democratic parenting is an ideal parenting style and has a significant influence on increasing children's emotional intelligence.